Rancang Bangun Teknologi Mesin Crumb Rubber dan Sistem Informasi Rantai Pasok untuk Mengolah Limbah Ban Bekas di Kota Semarang - Wijaya, S.T, M.Sc, A.MP, Dewa Kusuma; Santoso, Heru Agus; Islahudin, Nur (Jurnal Riptek, 2024)
Central Java, especially Semarang City, is one of the provincial capitals with quite high economic progress. These indicators can be seen through the high population dan the number of motorized vehicles as a mode of transportation. The high number of motorized vehicles can hurt the environment through pollution dan vehicle replacement waste. This research examines used tires as a type of waste produced from vehicle maintenance, which has become a polemic until now. This is because recycling is difficult dan has only been used as raw material for vulcanization or thrown into the environment. Through this research, the technology for processing used tire waste into crumb rubber products has become an effective response solution. Crumb rubber is a crumb rubber product that can be an industrial raw material with high economic value, where the selling price of crumb rubber is around IDR 65,000 per kg. On the other hdan, developing appropriate technology can provide added value for the environment by converting waste into raw material products to reduce impacts. Apart from that, there is added value from a social aspect because it provides new employment opportunities for related parties, namely the community as business actors who can partner with vehicle repair shops as waste providers. This research also designs a supply chain information system to support circular economic activities related to managing used tire waste into crumb rubber.